2013
DOI: 10.3109/10903127.2013.844872
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence-based Guideline for the Air Medical Transportation of Prehospital Trauma Patients

Abstract: Background. Decisions about the transportation of trauma patients by helicopter are often not well informed by research assessing the risks, benefits, and costs of such transport. Objective. The objective of this evidence-based guideline (EBG) is to recommend a strategy for the selection of prehospital trauma patients who would benefit most from aeromedical transportation. Methods. A multidisciplinary panel was recruited consisting of experts in trauma, EBG development, and emergency medical services (EMS) out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…13 The types of medications used also reflect airway management procedures with higher frequencies of sedatives and paralytics reported than in the other EMS level of care activations.…”
Section: Discussionmentioning
confidence: 99%
“…13 The types of medications used also reflect airway management procedures with higher frequencies of sedatives and paralytics reported than in the other EMS level of care activations.…”
Section: Discussionmentioning
confidence: 99%
“…37, 38 Recently, multiple stakeholder agencies developed guidelines for air medical transport of trauma patients using Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. 9 This effort was hampered by very low quality evidence, but recommended HEMS transport in patients meeting any physiologic or anatomic triage criteria from the National Field Triage Guidelines only when a significant time savings is present over GEMS transport. 9, 20 However, it is unclear from these guidelines what length of time would constitute a significant time savings.…”
Section: Discussionmentioning
confidence: 99%
“…9 This effort was hampered by very low quality evidence, but recommended HEMS transport in patients meeting any physiologic or anatomic triage criteria from the National Field Triage Guidelines only when a significant time savings is present over GEMS transport. 9, 20 However, it is unclear from these guidelines what length of time would constitute a significant time savings. Further, our group has shown that only a subset of the physiologic and anatomic triage criteria are useful for HEMS triage, based on improved survival for HEMS transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific results of this cooperative agreement effort are detailed in the remaining three EBG-related articles published in this issue. 5,6,7 The scientific contribution of these papers is without question. Although the application of evidence-based principles to prehospital protocol development is not new, never before has there been a uniform attempt to systematically incorporate such rigorous methodology as part of the initiation of a national process.…”
Section: Introduction Evidence-based Guidelines For Prehospital Practmentioning
confidence: 99%